توہین قرآن کے اسباب و وجوہات اور صورتیں: نصوص شریعہ کی روشنی میں تحقیقی جائزہ: Research Study: Causes, Reasons, and Forms of Quran Desecration: An Analytical Review in Light of Sharia Texts - Riaz Ahmed; Hafiz Abdul Wahab (International Research Journal of Arabic and Islamic Studies, 2024)
The desecration of the Quran is a deeply troubling phenomenon that elicits strong reactions from Muslim communities worldwide. This study aims to explore the underlying causes, reasons, and various forms of Quran desecration through an analytical review of Sharia texts. The research delves into historical and contemporary instances of Quran desecration, examining the motivations behind such actions, which range from political and ideological provocations to acts of sheer ignorance and misguidance. Through the lens of Sharia, the study categorizes the forms of desecration into deliberate acts of disrespect, inadvertent mishandling, and instances arising from a lack of understanding of the Quran's sanctity. By analyzing various jurisprudential opinions, the research highlights how Islamic scholars have historically addressed the issue, emphasizing the severe consequences of such actions in Islamic law. Furthermore, the study discusses the role of social, political, and cultural factors in exacerbating instances of Quran desecration. The research underscores the importance of educational initiatives aimed at fostering a deeper understanding of the Quran's sanctity among Muslims and non-Muslims alike. It also advocates for a proactive approach in addressing the root causes of Quran desecration through dialogue, education, and legal measures in accordance with Sharia. The findings suggest that a comprehensive understanding and respectful handling of the Quran can significantly reduce incidents of desecration. The study concludes with recommendations for policymakers, educators, and religious leaders to work collaboratively in promoting the reverence of the Quran and preventing its desecration in all forms.